2015
DOI: 10.1111/iju.12753
|View full text |Cite
|
Sign up to set email alerts
|

Sulfoquinovosylacylpropanediol is a novel potent radiosensitizer in prostate cancer

Abstract: Abbreviations & Acronyms α-SQMG = α-sulfoquinovosylmonoacylglycerol DAPI = 4´6´-diamindino-2-phenylindole dihydrochloride PBS = phosphate-buffered saline PCa = prostate cancer SMA = smooth muscle actin SQAP = sulfoquinovosylacylpropanediol XRT = X-ray irradiation Objectives: To examine the effects of combined treatment with sulfoquinovosylacylpropanediol and X-ray irradiation on the remodeling of the prostate cancer microenvironment, including angiogenic and hypoxic characteristics. Methods: Human prostate can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…We recently reported that the novel XRT radiosensitizer, SQAP, enhanced growth inhibition in a xenotransplantation mouse model of human PCa . Our findings showed great potential for SQAP as a radiosensitizer in PCa through its ability to oxygenate tumor tissues by the induction of VN; additionally, the effect of tumor site oxygenation persisted at even 30 days after XRT + SQAP treatment.…”
mentioning
confidence: 56%
“…We recently reported that the novel XRT radiosensitizer, SQAP, enhanced growth inhibition in a xenotransplantation mouse model of human PCa . Our findings showed great potential for SQAP as a radiosensitizer in PCa through its ability to oxygenate tumor tissues by the induction of VN; additionally, the effect of tumor site oxygenation persisted at even 30 days after XRT + SQAP treatment.…”
mentioning
confidence: 56%
“…23). Sawada and colleagues (24) demonstrated that the tumor volume in xenograft models of the human prostate cell lines DU145 and PC3 was reduced after a combination of SQAP administration and radiotherapy. PC3 tumors were fully eradicated by radiation alone, and therefore did not benefit from the addition of SQAP, while DU145 tumors showed little if any response to XRT, but substantial response to SQAP.…”
Section: Introductionmentioning
confidence: 99%
“…1 To understand the interesting findings of this study, knowledge of SQAP is required. SQAP is a sulfoglyco-lipid originally derived from sea urchins expressing α-sulfoquinovosylmonoacylglycerol (SQMG).…”
mentioning
confidence: 99%
“…In the present article, Sawada et al showed that combined treatment with sulfoquinovosylacylpropanediol (SQAP) and X-ray irradiation remodeled the microenvironment in prostate cancer. 1 To understand the interesting findings of this study, knowledge of SQAP is required. SQAP is a sulfoglyco-lipid originally derived from sea urchins expressing α-sulfoquinovosylmonoacylglycerol (SQMG).…”
mentioning
confidence: 99%